Tissue deposition and toxicological effects of commercially significant rare earth oxide nanomaterials: Material and physical properties. Issue 3 (3rd June 2016) - Das, Soumen; Reed McDonagh, Philip; Selvan Sakthivel, Tamil; Barkam, Swetha; Killion, Kelsey; Ortiz, Julian; Saraf, Shashank; Kumar, Amit; Gupta, Ankur; Zweit, Jamal; Seal, Sudipta
ABSTRACT: Rare earth oxide (REO) materials are found naturally in earth's crust and at the nanoscale these REO nanoparticles exhibit unique thermal, electrical, and physicochemical properties. REO nanoparticles are widely used in different industrial sectors for ceramics, glass polishing, metallurgy, lasers, and magnets. Recently, some of these REO nanoparticles have been identified for their potential application in medicine, including therapy, imaging, and diagnostics. Concurrent research into the REO nanomaterials' toxicities has also raised concern for their environmental impacts. The correlation of REO nanoparticles mediated toxicity with their physiochemical properties can help to design nanoparticles with minimal effect on the environment and living organisms. In vitro assay revealed toxicity toward Human squamous epithelial cell line (CCL30) and Human umbilical vascular endothelial cells (HUVEC) at a concentration of 100 µM and higher. In vivo results showed, with the exception of CeO2 and Gd2 O3, most of the naoparticles did not clear or had minimum clearance (10–20%) from the system. Elevated levels of alanine transferase were seen for animals given each different nanoparticle, however the increases were not significant for CeO2 and Dy2 O3 . Nephrotoxicity was only seen in case of Dy2 O3 and Gd2 O3 . Lastly, histological examination revealed presence of swollen hepatocytes which further confirms toxicity of the commercial REO nanomaterials. The in vivo toxicity is mainly due to excessive tissue deposition (70–90%) due to the commercial REO nanoparticles' poor physical properties (shape, stability, and extent of agglomeration). Therefore, optimization of nanoparticles physical properties is very important. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 904–917, 2017.